Comparative Metabolomic Sampling of Upper and Lower Airways by Four Different Methods to Identify Biochemicals That May Support Bacterial Growth - Farne, Hugo; Groves, Helen T.; Gill, Simren K.; Stokes, Isobel; McCulloch, Scott; Karoly, Edward; Trujillo-Torralbo, Maria-Belen; Johnston, Sebastian L.; Mallia, Patrick; Tregoning, John S. (Frontiers in Cellular and Infection Microbiology, 2018)
Bacteria need nutrients from the host environment to survive, yet we know little about which biochemicals are present in the airways (the metabolome), which of these are essential for bacterial growth and how they change with airway disease. The aims of this pilot study were to develop and compare methodologies for sampling the upper and lower airway metabolomes, to determine whether the upper airway metabolome was reflective of the lower airway and to identify biochemicals present in the airways that could potentially support bacterial growth. Eight healthy human volunteers were sampled by four methods: two standard approaches - nasal lavage and induced sputum, and two using a novel platform, synthetic adsorptive matrix (SAM) strips - nasosorption and bronchosorption. Collected samples were analysed by Ultrahigh Performance Liquid Chromatography-Tandem Mass Spectroscopy (UPLC-MS/MS). 581 biochemicals, belonging to a range of metabolomic super-pathways, were recovered from the airways. We observed significant differences in the upper and lower airway metabolomes. Significantly more biochemicals were recovered when SAM strips were used, compared to standard sampling techniques. Many of the biochemicals that support bacterial growth were significantly more abundant in the upper than the lower airways. This work demonstrates for the first time that SAM strips are a highly effective method for sampling the airway metabolome and that the metabolomic profile of the upper airway does not completely reflect the lower airway. This work will assist further studies to understand how changes in the airway metabolome affect bacterial infection in patients with underlying airway disease.